Prevzemanje besed v slovenščini - Pogačnik, Aleš (Jezik in slovstvo, 2003)
The Slovene language does not have any fixed rules for borrowing foreign words. There are some orthographic rules concerning the borrowing of foreign words, but both of usage of written Slovene and the rules, which are over 20 years old, demonstrate numerous inconsistencies. The article, based on years of experience in the editing of lexikographic books, recapitulates the inconsistencies, unnecessary complications and deficiencies of the Slovene orthographic rules on borrowing, especially of personal names, oand offers an alternative guideline.
Keywords: Slovene; slovenščina; leksikologija; lexicology; tujke; orthography; pravopis